Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - De Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.